1968
DOI: 10.1111/j.1476-5381.1968.tb07949.x
|View full text |Cite
|
Sign up to set email alerts
|

The biological properties of the optical isomers of propranolol and their effects on cardiac arrhythmias

Abstract: 1. The optical isomers of propranolol have been compared for their f,-blocking and antiarrhythmic activities.2. In blocking the positive inotropic and chronotropic responses to isoprenaline, ( +)-propranolol had less than one hundredth the potency of (-)-propranolol. At dose levels of (+ )-propranolol which attenuated the responses to isoprenaline, there was a significant prolongation of the PR interval of the electrocardiogram. 3. The metabolic responses to isoprenaline in dogs (an increase in circulating glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
197
0
5

Year Published

1974
1974
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 573 publications
(214 citation statements)
references
References 18 publications
12
197
0
5
Order By: Relevance
“…Thus, YB-2 and its optical isomers appear to have a similar potency ratio for anti arrhythmic activity as is the case with propranolol and its optical isomers (5,11,20,37).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Thus, YB-2 and its optical isomers appear to have a similar potency ratio for anti arrhythmic activity as is the case with propranolol and its optical isomers (5,11,20,37).…”
Section: Discussionmentioning
confidence: 97%
“…Recently the association between antiarrhythmic activity against ouabain-induced cardiac disturbances and local anesthetic activity, and the dissociation between the for mer property and beta-receptor blockade have been questioned by several investigators (20,24,25). Burrett and Cullum (20) It has been also reported that an increased release of catecholamines from the heart and adrenal glands by the ad ministration of ouabain may be an important factor in this type of arrhythmia (33,34).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This unspecific effect might have contributed to the strong bradycardia in addition to the ~3-adrenergic blocking activity. The /3-antagonistic property of d,l-propranolol, however, is due mainly to the 1-isomer, while the d-isomer of propranolol has only weak/~-antagonist activity, and both exhibit equivalent local anesthetic activity (Howe and Shanks, 1966;Barrett and Cullum, 1968).…”
Section: Discussionmentioning
confidence: 99%